2021
DOI: 10.3390/biomedicines9060587
|View full text |Cite
|
Sign up to set email alerts
|

Current Understanding of the Immunomodulatory Activities of High-Density Lipoproteins

Abstract: Lipoproteins interact with immune cells, macrophages and endothelial cells - key players of the innate and adaptive immune system. High-density lipoprotein (HDL) particles seem to have evolved as part of the innate immune system since certain HDL subspecies contain combinations of apolipoproteins with immune regulatory functions. HDL is enriched in anti-inflammatory lipids, such as sphingosine-1-phosphate and certain saturated lysophospholipids. HDL reduces inflammation and protects against infection by modula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 312 publications
(393 reference statements)
0
24
0
Order By: Relevance
“…As a snapshot of the steady-state plasma cholesterol levels, HDL-C levels do not provide direct information on the rate of cholesterol efflux from vascular macrophages to the liver, which is influenced by many factors beyond the mass of HDL-C alone. Therefore, circulating HDL-C concentrations do not provide information about the structure and composition of HDL and anti-inflammatory, antioxidant, antithrombotic, and endothelial function-promoting activities of HDL ( 13 15 ), although there is increasing evidence of the clinical importance of these pleiotropic functions ( 16 ). Therefore, current research strategies focus on improving the atheroprotective functions of HDL.…”
Section: Introductionmentioning
confidence: 99%
“…As a snapshot of the steady-state plasma cholesterol levels, HDL-C levels do not provide direct information on the rate of cholesterol efflux from vascular macrophages to the liver, which is influenced by many factors beyond the mass of HDL-C alone. Therefore, circulating HDL-C concentrations do not provide information about the structure and composition of HDL and anti-inflammatory, antioxidant, antithrombotic, and endothelial function-promoting activities of HDL ( 13 15 ), although there is increasing evidence of the clinical importance of these pleiotropic functions ( 16 ). Therefore, current research strategies focus on improving the atheroprotective functions of HDL.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of prospective cohort studies showed that high HDL-C levels reduced the incidence of stroke ( 24), while low HDL-C levels were associated with higher stroke severity and poor clinical prognosis (25). Studies have shown that HDL-C regulates the activity of a variety of inflammatory cells, including neutrophils and eosinophils (26). Further studies have shown that HDL-C can inhibit neutrophil activity and transformation (10).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from population studies as well as experiments in genetic animal models points to the importance of CETP in this process (Blauw et al 2020;Trinder et al 2019Trinder et al , 2021. However also HDL particles per se as well as specific structural components of HDL exert several antibacterial activities such as binding and removal of lipopolysaccharides, protection of epithelial and endothelial barriers, or modulatory effects on leukocyte functions (Catapano et al 2014;Meilhac et al 2020;Pirillo et al 2015;Robert et al 2021;Rohatgi et al 2021;Trakaki and Marsche 2021). The special association of HDL-C with gastroenteritis may also mirror an important role of HDL that is locally produced in the intestine (Ko et al 2020).…”
Section: Infectionsmentioning
confidence: 99%
“…Neither are the mechanisms understood. They may involve immunomodulatory effects of HDL which are relevant in the development of auto-immunity (Catapano et al 2014;Pirillo et al 2015;Rohatgi et al 2021;Trakaki and Marsche 2021) or protective effects of HDL towards organs attacked by the immune system so that the onset of organ damage or failure and thereby the clinical diagnosis of manifest disease is delayed. For example, the anti-apoptotic effects of HDL on pancreatic beta cells may delay the loss of insulin production in the course of progressing type 1 diabetes (von Eckardstein and Widmann 2014;Yalcinkaya et al 2020).…”
Section: Autoimmune Diseasesmentioning
confidence: 99%